Endocrine Complications in Hepatic Glycogen Storage Diseases: A Long-term Perspective - Kim, Ja Hye; Lee, Yena; Hwang, Soojin; Kim, Dohyung; Lee, Beom Hee; Kim, Gu-Hwan; Yoo, Han-Wook; Choi, Jin-Ho (Experimental and Clinical Endocrinology & Diabetes, 2025)
Patients with a hepatic type of glycogen storage diseases (GSDs) can manifest endocrine features such as hypoglycemia, dyslipidemia, or osteoporosis. This study aimed to investigate the long-term endocrine consequences in patients with hepatic GSDs.This study included 64 patients from 52 families with hepatic GSDs including GSD type Ia (41 patients from 37 families), Ib (3 unrelated), III (8 from 6 families), IV (1 patient), and IX (11 from 5 families). All patients were genetically confirmed. Clinical and endocrine findings were retrospectively analyzed.The median age at diagnosis and current age were 2.4 years (range, 0.1−42.4 years) and 17.6 years (range, 1.0−47.8 years), respectively. The mean height SDS at diagnosis was –3.5±1.4, and short stature was observed in 35.6% of patients. Patients diagnosed after the age of 3.4 years exhibited a high risk of short stature (OR=36.1; P-value<0.001). Among 33 patients who reached the final height, 23 (69.7%) showed delayed puberty. Hypertriglyceridemia was observed in 46 patients (71.9%), whereas 25 patients (39%) had elevated low-density lipoprotein cholesterol levels during the follow-up period. Among 24 patients who underwent dual-energy X-ray absorptiometry, 22 showed a low bone mineral density Z-score of –3.0±1.3 at the L-spine.This study described the long-term endocrine consequences in patients with hepatic GSDs. Pediatric endocrinologists should be aware of the presenting features and long-term endocrine sequelae of GSDs to provide proper management and decrease its morbidities.
Keywords: Glycogen storage disease; short stature; delayed puberty; osteoporosis; hypertriglyceridemia